PENINGKATAN KETERAMPILAN KOLABORASI MELALUI PEMBELAJARAN KOOPERATIF JIGSAW DI KELAS V SEKOLAH DASAR - Alfinatusya'diyah, Fauriza Tahta; Hendratno; Nuryani, Bekti; Mahalisa Dyah Prostanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The use of learning models that have not created a learning atmosphere that creates passive students has an impact on students' collaboration skills. The purpose of this study was to improve collaboration skills through jigsaw cooperative learning in grade V elementary school. The type of research used was collaborative classroom action research (CCA) conducted over two cycles which included planning, implementation observation and reflection. The collection techniques used were questionnaires and observation. The results of this PTKK found that the learning process using the jigsaw cooperative learning model proved to be able to improve students' collaboration skills. This can be proven by the acquisition of questionnaire data related to students' responses related to collaboration skills. In the pre-cycle, an average of 48.92% was obtained, then there was an increase in cycle I and cycle II with an average of 70.08% and 88.44%. From the response questionnaire data obtained in cycle I and II, it shows an increase of 18.36%. Therefore, this research has implications for the learning process that can be used by teachers as teacher feedback and learning models that can facilitate students.